Cortical and Cerebellar Oscillatory Responses to Postural Instability in Parkinson's Disease - Bosch, Taylor J.; Kammermeier, Stefan; Groth, Christopher; Leedom, Matt; Hanson, Elizabeth K.; Berg-Poppe, Patti; Singh, Arun (Frontiers in Neurology, 2021)
Introduction: Posture and balance dysfunctions critically impair activities of daily living of patients with progressing Parkinson’s disease (PD). However, the neural mechanisms underlying postural instability in PD are poorly understood, and specific therapies are lacking. Previous electrophysiological studies have shown distinct cortical oscillations with a significant contribution of the cerebellum during postural control tasks in healthy individuals. Methods: We investigated cortical and mid-cerebellar oscillatory activity via electroencephalography (EEG) during a postural control task in 10 PD patients with postural instability (PDPI+), 11 PD patients without postural instability (PDPI–), and 15 age-matched healthy control participants. Relative spectral power was analyzed in the theta (4-7 Hz) and beta (13-30 Hz) frequency bands. Results: Time-dependent postural measurements computed by accelerometer signals showed poor performance in PDPI+ participants. EEG results revealed that theta power was profoundly lower in mid-frontal and mid-cerebellar regions during the postural control task in PDPI+, compared to PDPI– and control participants. In addition, theta power was correlated with postural control performance in PD subjects. No significant changes in beta power were observed. Additionally, oscillatory changes during the postural control task differed from the resting state. Conclusion: This study underlines the involvement of mid-frontal and mid-cerebellar regions in postural stability during a balance task and emphasizes the important role of theta oscillations therein for postural control in PD.